Adropin Slightly Modulates Lipolysis, Lipogenesis and Expression of Adipokines but Not Glucose Uptake in Rodent Adipocytes - Mariami Jasaszwili (Genes, 2021)
Adropin is a peptide hormone which modulates energy homeostasis and metabolism. In animals with diet-induced obesity, adropin attenuates adiposity and improves lipid and glucose homeostasis. Adropin promotes the proliferation of rodent white preadipocytes and suppresses their differentiation into adipocytes. By contrast, the effects of adropin on mature white adipocytes are unknown. Therefore, we aimed to evaluate the effects of adropin on lipolysis, lipogenesis and glucose uptake in white rodent adipocytes. We assessed the effects of adropin on the mRNA expression of adiponectin, resistin and visfatin. White preadipocytes were isolated from male Wistar rats. Differentiated 3T3-L1 cells were used as a surrogate model of white adipocytes. Lipolysis was measured by the evaluation of glycerol and free fatty acid secretion using colorimetric kits. The effects of adropin on lipogenesis and glucose uptake were measured using radioactive-labelled glucose. The expression of adipokine mRNA was studied using real-time PCR. Our results show that adropin slightly promotes lipolysis in rat adipocytes and 3T3-L1 cells. Adropin suppresses lipogenesis in rat adipocytes without influencing glucose uptake. In addition, adropin stimulates adiponectin mRNA expression and suppresses the expression of resistin and visfatin. These results indicate that adropin may be involved in controlling lipid metabolism and adipokine expression in white rodent adipocytes.